RATING RESULTS for Malaysian Higher Education Institution Rating System 2011 SETARA - New Sabah Times English, (KK) (New Sabah Times English (KK), 2012)
On 1 November 2012, Higher Education Minister Datuk Seri Mohamad Khaled Nordin announced the results of SETARA '11, a rating exercise carried out on higher education institutions (HEIs) in Malaysia by the Malaysian Qualifications Agency (MQA); and the Malaysia Research Assessment Instrument(MyRA®) 2011 carried out by the Ministry of Higher Education (MOHE).